Analisis Penyebab Konstipasi Pada Ibu Hamil Di Wilayah Kerja Puskesmas Payung Sekaki Pekanbaru - Busyra Hanim (STIKes Payung Negeri Pekanbaru, 2019)
Constipation is one of the incoveniences that pregnant women often complain about. If not managed properly constipation can cause serious complication. 40% of pregnant women have experienced constipation. In Pekanbaru constipation is experienced by about 4-30% of pregnant women. The purpose of this study was to analyze the causes of constipation in pregnant women in The Payung Sekaki Puskesmas Work Area Pekanbaru. The study was conducted on 96 respondents in the Work Area Payung Sekaki Puskesmas Pekanbaru taken by purposive sampling technique. This research is quantitative with descriptive design. The results showed that constipation in pregnant women in The Payung Sekaki Puskesmas Work Area was caused by consumption of Fe tablets of 71 poeple (74%), risky eating patterns of 71 poeple (74%), squating position when defecating of 40 poeple (42%), physical activity/sports of 46 poeple (48%), and the habit of delaying the desire to defecate of 50 poeple (52%). Suggestions for health workers in the Payung Sekaki Health Center in Pekanbaru to study in full identify the cause of constipation complained in order to provide appropriate education in managing this discomfort.